Transforming Mathematics Education: Navigating Digital Barriers in Classrooms (Interdisciplinary Research in Education, 2025)
The nature of mathematics courses often appears complex for the integration of digital technology in classrooms. Practicing digital technology within transformative pedagogy enables students to become self-reliant, self-motivated, and engaged in learning-by-doing. However, its proper implementation in the context of Nepal remains constrained by inadequate infrastructure, such as the lack of computer and mathematics laboratories, unreliable internet facilities, and insufficient institutional support. Traditional methods of teaching, such as drawing figures on the board and relying solely on problem-solving strategies, dominate the classroom practice, limiting the scope of transformative pedagogy. Although some teachers use laptops, projectors, and PowerPoint slides to foster critical thinking and creativity, these efforts remain insufficient to achieve meaningful transformation. This study indicates that digital technology, when practiced effectively in transformative pedagogy, serves as the backbone of sustainable mathematics learning. Even though challenges such as outdated curricula, economic constraints of students, and limited digital-friendly classrooms continue to impede progress. Student experiences during COVID-19, however, demonstrated the potential of digital platforms like Zoom, Messenger, GeoGebra, and Mathematica to create collaborative and engaging learning environments despite existing barriers. The findings suggest that digital technology is not only a tool for solving mathematical problems but also a medium for cultivating curiosity, collaboration, and transformative learning. The implications point toward the urgent need for a sustainable digital plan that emphasizes blended learning, equitable access, and inclusive engagement in mathematics education in Nepal.